2023
DOI: 10.1101/2023.01.23.22283996
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Personalized Inhaled Bacteriophage Therapy Decreases Multidrug-ResistantPseudomonas aeruginosa

Abstract: Bacteriophage therapy, which uses lytic viruses as antimicrobials, has received renewed interest to address the emerging antimicrobial resistance (AMR) crisis. Cystic fibrosis (CF), a disease complicated by recurrent P. aeruginosa pulmonary infections that cause lung function decline, is an example where AMR is already a clinical problem. While bacteria evolve bacteriophage resistance, we developed a strategy to select bacteriophages that target bacterial cell surface receptors that contribute to antibiotic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…To model phage therapy in the CF airways, we utilized a panel of P. aeruginosa phages that have been used therapeutically in pwCF under FDA emergency use authorization and in a clinical trial (NCT04684641) to treat chronic MDR P. aeruginosa infections (23). We complemented this panel with additional P. aeruginosa phages obtained from hospital wastewater that have lytic activity against various P. aeruginosa clinical isolates from pwCF that were isolated for use in therapeutic applications (24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To model phage therapy in the CF airways, we utilized a panel of P. aeruginosa phages that have been used therapeutically in pwCF under FDA emergency use authorization and in a clinical trial (NCT04684641) to treat chronic MDR P. aeruginosa infections (23). We complemented this panel with additional P. aeruginosa phages obtained from hospital wastewater that have lytic activity against various P. aeruginosa clinical isolates from pwCF that were isolated for use in therapeutic applications (24).…”
Section: Resultsmentioning
confidence: 99%
“…To model phage therapy in the CF airways, we utilized a panel of P. aeruginosa phages that have been used therapeutically in pwCF under FDA emergency use authorization and in a clinical trial (NCT04684641) to treat chronic MDR P. aeruginosa infections (23).…”
Section: Panel Of Therapeutic P Aeruginosa Lytic Bacteriophages Is Ge...mentioning
confidence: 99%
“…aeruginosa phages that have been used therapeutically in pwCF under U.S. Food and Drug Administration (FDA) emergency use authorization and in a clinical trial (NCT04684641) to treat chronic MDR P . aeruginosa infections [ 23 ]. We complemented this panel with additional P .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Chan et al . showed that, by applying personalized phage therapy, they could decrease virulence and effectively re-sensitize P. aeruginosa strains against multiple antibiotics ( 81 ). By twisting evolution in their favor, they could improve antibiotic treatment and therapeutic outcome further underlining the importance of a phage-antibiotic combination therapy, especially in a patient-tailored approach.…”
Section: Discussionmentioning
confidence: 99%